Patient‐assigned health utility values for controlled and uncontrolled pemphigus vulgaris and foliaceus. (26th July 2019) - Hajdu, K.; Brodszky, V.; Stalmeier, P.F.M.; Ruzsa, G.; Tamási, B.; Gulácsi, L.; Péntek, M.; Sárdy, M.; Bata‐Csörgő, Z.; Kinyó, Á.; Szegedi, A.; Rencz, F.
Abstract: Background: The assessment of health‐related quality of life (HRQoL) in patients with pemphigus is now of increasing interest due to the availability of highly effective new therapies. Preference‐based HRQoL values or health utilities required for medical and financial decision‐making are not yet available directly from pemphigus patients. Objective: To obtain health utility values for current health and hypothetical health states from the perspective of pemphigus patients. Methods: A cross‐sectional questionnaire survey was carried out with pemphigus patients. Disease severity was rated by Autoimmune Bullous Skin Disorder Intensity Score (ABSIS). Patients were asked to evaluate their current health as well as three common hypothetical pemphigus health states [uncontrolled pemphigus vulgaris (PV), uncontrolled pemphigus foliaceus (PF) and controlled PV/PF] by using composite time trade‐off (cTTO). Multiple regression was applied to explore determinants of utility values. Results: Responses of 108 patients (64.8% women, mean age 57.4 years) were analysed. Mean ABSIS score was 11.6. The mean utility values for the hypothetical uncontrolled PV, uncontrolled PF and controlled PV/PF health states were 0.41, 0.52 and 0.66 with cTTO. The mean cTTO scores for current health were higher compared with the hypothetical health states (0.76; P  < 0.001). Patients with higher ABSIS, worse pain intensity scores and those having a caregiver reported lower utility values for current health ( P  < 0.05). Conclusions: In pemphigus, HRQoL impairment expressed in utility values seems to be considerable, especially in comparison with other chronic dermatological conditions (e.g. psoriasis, atopic eczema, chronic hand eczema). These health utilities inform physicians, policymakers and funders about the overall extent of health loss in pemphigus and provide evidence to guide medical decisions and cost‐effectiveness analyses of treatment strategies. Future research is needed to evaluate the caregiver burden in pemphigus.